Adult obesity: personality traits, eating behaviour, physical activity, DRD2 polymorphisms and health related quality of life in a Malaysia private university - Lim, Zhi Meng (2021)
Obesity is a worldwide issue with high prevalence rate up to 64% and 65% of obese or overweight male and female population in Malaysia, respectively. National Health and Morbidity Survey 2019 reported that 50.1% of adults in Malaysia were overweight or obese, with 30.4% being overweight and 19.7% obese (NHMS 2019). This study aims to investigate the aetiology of obesity as obesity is believed to present a risk to health (chronic diseases and psychological disorders). It was hypothesized that there is a correlation of obesity with dopamine receptor D2 (DRD2) Taq1 gene polymorphism, personality traits, eating behaviour, physical activity and quality of life. DRD2 gene is selected as reduced D2 receptor activity generates a reward deficiency and alters appetitive motivation, which may induce compulsive eating and contributes to obesity (Beeler et al., 2016). The study cohort consisted of 394 subjects (125 males and 269 females) who studied or worked in University Tunku Abdul Rahman (UTAR), Malaysia. Personality traits, eating behaviours and physical activity were examined by using Mini International Personality Item Pool (IPIP), Three-Factor Eating Questionnaire-R18 (TFEQ-R18) and International Physical Activity Questionnaire (IPAQ), respectively. The Motives for Physical Activity Measure – Revised (MPAM-R) were used to assess the strength of five motives for participating in physical activities. The Short Form General Health Questionnaire (SF-36) was used to examine the quality of life. Body mass index (BMI) of the participants was examined to evaluate obesity status. Genotyping of Taq1 gene polymorphisms (ANKK1/DRD2 Taq1A, DRD2 Taq1B and DRD2 Taq1D) was performed by PCR-RFLP using the genomic DNAs extracted from mouthwash samples. Statistical analysis was done by using SPSS, AMOS and Stats Tools Package. Cognitive restraint (CR), uncontrolled eating (UE) and emotional eating (EE) showed significant correlations on neuroticism. UE and EE were significantly correlate with conscientiousness while EE was significantly correlated with extraversion. Extraversion trait was predominantly seen among underweight and normal BMI individuals and with positive correlation correlated with physical activity. Underweight and Normal individuals were more prone to emotional eating. Obesity is significantly associated with physical activity. DRD2 Taq1A, Taq1B and Taq1D polymorphisms did not exerted as the moderator in eating behaviour, physical activity and obesity. There is no significant difference between obesity and health related quality of life (HRQoL). In conclusion, extraversion is correlated to being physically active and decreased emotional eating. Hence, people are encouraged to take the initiatives to forge meaningful connections with others and maintain an energetic lifestyle, which in turn lower the rate of obesity. In addition, Taq1 genotypes showed significant differences on motives for participating in physical activities but not physical activity level. This suggested that innate genetic factor alone does not help in preventing obesity. Postnatal initiative is required for individuals to execute physical activities in order to achieve a healthy BMI.